Anatomical and histological study of the alimentary tract in fruit bats (Rousettus amplexicaudatus) - Yeni Dhamayanti; Agung Mujiburrahman; Muhammet Bayram; Lintang Winantya Firdausy (Jurnal Medik Veteriner, 2026)
This study presents a comprehensive gross anatomical and histological characterization of the alimentary tract in the fruit bat (Rousettus amplexicaudatus), a frugivorous megachiropteran species whose digestive morphology remains incompletely described. Seven adult bats (four males, three females) were captured in Banyuwangi, East Java, and examined through standardized morphometric, gross anatomical, and histometric analyses. Euthanasia was performed using Xylazine and Ketamine, followed by systematic dissection and measurement of body and visceral parameters. Histological preparations of the esophagus, stomach, duodenum, jejunum, ileum, and colon were stained with hematoxylin and eosin and evaluated microscopically. Results revealed minimal sexual dimorphism in external and internal morphometric traits, except for a significantly longer esophagus in males (p < 0.05). Gross anatomy showed a simple, glandular stomach and an elongated intestinal tract, consistent with adaptations for rapid carbohydrate digestion. Histomorphometric evaluation indicated comparable mucosal and muscular thickness between sexes, suggesting functional uniformity in digestive performance. Histological observations identified a stratified squamous esophageal lining, glandular gastric mucosa, prominent intestinal villi with crypts of Lieberkühn, and well-developed Peyer’s patches, highlighting efficient nutrient absorption and mucosal immune function. Overall, the findings demonstrate that fruit bat possesses a structurally specialized yet sexually consistent digestive system optimized for frugivory. This integrative dataset fills critical gaps in bat digestive morphology, providing a standardized anatomical and histological reference for comparative physiology, dietary adaptation, and host–pathogen interaction studies in megachiropteran bats.